IP3R-Mediated Compensatory Mechanism for Calcium Handling in Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes With Cardiac Ryanodine Receptor Deficiency - Luo, Xiaojing; Li, Wener; Künzel, Karolina; Henze, Sarah; Cyganek, Lukas; Strano, Anna; Poetsch, Mareike S.; Schubert, Mario; Guan, Kaomei (Frontiers in Cell and Developmental Biology, 2020)
In adult cardiomyocytes (CMs), the type 2 ryanodine receptor (RYR2) is an indispensable Ca2+ release channel that ensures the integrity of excitation-contraction coupling, which is fundamental for every heartbeat. However, the role and importance of RYR2 during human embryonic cardiac development are still poorly understood. Here, we generated two human induced pluripotent stem cell (iPSC)-based RYR2 knockout (RYR2–/–) lines using the CRISPR/Cas9 gene editing technology. We found that RYR2–/–-iPSCs could differentiate into CMs with the efficiency similar to control-iPSCs (Ctrl-iPSCs); however, the survival of iPSC-CMs were markedly affected by the lack of functional RYR2. While Ctrl-iPSC-CMs exhibited regular Ca2+ handling, we observed significantly reduced frequency and intense abnormalities of Ca2+ transients in RYR2–/–-iPSC-CMs. Ctrl-iPSC-CMs displayed sensitivity to extracellular Ca2+ ([Ca2+]o) and caffeine in a concentration-dependent manner, while RYR2–/–-iPSC-CMs showed inconsistent reactions to [Ca2+]o and were insensitive to caffeine, indicating there is no RYR2-mediated Ca2+ release from the sarcoplasmic reticulum (SR). Instead, compensatory mechanism for calcium handling in RYR2–/–-iPSC-CMs is partially mediated by the inositol 1,4,5-trisphosphate receptor (IP3R). Similar to Ctrl-iPSC-CMs, SR Ca2+ refilling in RYR2–/–-iPSC-CMs is mediated by SERCA. Additionally, RYR2–/–-iPSC-CMs showed a decreased beating rate and a reduced peak amplitude of L-type Ca2+ current. These findings demonstrate that RYR2 is not required for CM lineage commitment but is important for CM survival and contractile function. IP3R-mediated Ca2+ release is one of the major compensatory mechanisms for Ca2+ cycling in human CMs with the RYR2 deficiency.